Post-Thaw Preservation of Anti-Microbial Lactobacillus rhamnosus and Saccharomyces boulardii Metabolite Complexes - Isayenko, Olena (Problems of Cryobiology and Cryomedicine, 2020)
The paper demonstrates an antimicrobial eﬀect of metabolite complexes of Lactobacillus rhamnosus GG and Saccharomyces boulardii, obtained by own method, after 6 months’ storage in a frozen state (−23 ± 1ºС) in respect of Staphylococcus aureus, Staphylococcus haemoliticus, Enterococcus faecalis, Corynebacterium xerosis with multidrug resistance. Increase in diameters of growth inhibition zones (by (3.0 ± 0.4)–(6.1 ± 0.3) mm) for all the investigated pathogens under the inﬂuence of metabolite complexes (freshly obtained and after storage) with azithromycin has been proven. No signiﬁcant diﬀerence in antimicrobial activity of antibacterial agents with freshly obtained complexes and after storage at (−23 ± 1)°C was found. The expediency of using the chosen storage method to design the brand new products as well as development of ‘auxiliary drugs’ for antibiotics was conﬁrmed. Probl Cryobiol Cryomed 2020; 30(4): 343–358